The Separation of AHF from Fibrinogen - van Creveld, S; Veder, H. A; Pascha, C. N; Kroeze, W. F (Thrombosis and Haemostasis, 1959)
Anti-haemophilic globulin and fibrinogen of both bovine and human origin could be separated on columns of DEAE-cellulose. The yield of bovine AHF was high in contrast to that of human AHF, but further work to improve this yield is in progress.